2018
DOI: 10.1038/s12276-018-0169-z
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin B1 stability is increased by interaction with BRCA1, and its overexpression suppresses the progression of BRCA1-associated mammary tumors

Abstract: Germline BRCA1 mutations predispose women to breast and ovarian cancer. BRCA1, a large protein with multiple functional domains, interacts with numerous proteins involved in many important biological processes and pathways. However, to date, the role of BRCA1 interactions at specific stages in the progression of mammary tumors, particularly in relation to cell cycle regulation, remains elusive. Here, we demonstrate that BRCA1 interacts with cyclin B1, a crucial cell cycle regulator, and that their interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Previous studies have implicated the role of Cyclin B1 in the regulation of cell proliferation in breast cancer. [35][36][37] In our study, the results indicated that Aurora A-Cyclin B1 axis plays a crucial role in obesity breast cancer. The degree of heterogeneity and the expression pattern of biomarkers under study may constitute a potential problem in tissue microarray-based study.…”
Section: Dovepresssupporting
confidence: 54%
“…Previous studies have implicated the role of Cyclin B1 in the regulation of cell proliferation in breast cancer. [35][36][37] In our study, the results indicated that Aurora A-Cyclin B1 axis plays a crucial role in obesity breast cancer. The degree of heterogeneity and the expression pattern of biomarkers under study may constitute a potential problem in tissue microarray-based study.…”
Section: Dovepresssupporting
confidence: 54%
“…Freitas et al (2016) thought hierridin B was a potential anticancer compound that targeted CCNB1. A study in breast cancer confirmed that targeting CCNB1 was useful in BRCA1-associated breast cancer therapy (Choi et al, 2018). In clinical, Resveratrol (Joe et al, 2002), quercetin (Choi et al, 2001), and genistein (Wiseman et al, 2007) were the representative targeted drugs.…”
Section: Discussionmentioning
confidence: 94%
“…Treszezamsky et al found that BRCA1-and BRCA2-deficient cells are sensitive to Etoposide, which targeting topoisomerase II (TOP2A) and inducing DNA double-strand breaks [27]. High expression of CCNB1 was also observed in BRCA1-mutant cancer and induction of vinblastine targeting CCNB1 could significantly reduce tumor progression [28]. BRCA2 could interact with Filamin A actin-binding protein, further recruiting endosomal sorting complex required for transport (ESCRT)-associated proteins, Alix and Tsg101, and forming CEP55-Alix and CEP55-Tsg101 complexes at the midbody.…”
Section: Discussionmentioning
confidence: 99%